A study on freezing technology for the safe storage and transportation of spent lithium-ion batteries - Yeo, Yong-Ho; Wang, Jei-Pil (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates cryogenic freezing as a safety measure for end-of-life (EOL) lithium-ion batteries during storage and transportation. We consider immersion and indirect heat-exchange architectures compatible with liquid nitrogen (LN₂) or liquefied air (LA), and evaluate pre-/post-freezing changes in module-level properties. Electrical diagnostics focus on early degradation indicators—charge/discharge capacity, direct-current internal resistance (DCIR), and insulation resistance—measured under matched protocols before and after freezing. Under the tested protocol (−50 °C, ≥24 h soak, controlled ramp, electrical isolation, gradual rewarming), no macroscopic mechanical damage was observed, and the module retained its electrochemical performance: discharge capacity remained essentially unchanged, DCIR showed no measurable increase, and insulation resistance stayed ≥ 500 MΩ. These results indicate that short-term low-temperature storage can be implemented without compromising subsequent electrical behavior, supporting the feasibility of cryogenic strategies as a risk-mitigation approach for EOL battery logistics. The findings provide baseline data for future module/pack-scale demonstrations, repeated freeze–thaw durability assessments, and comparative studies using LN₂- or LA-based cooling systems.